2009
DOI: 10.4103/0019-509x.52964
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating duct carcinoma within a fibroadenoma

Abstract: InÞ ltrating duct carcinoma within a Þ broadenomaSir Fibroadenoma may rarely be associated with breast cancer, lobular or ductal carcinoma in situ. [1] Infiltrating duct carcinoma (IDC) arising within a fibroadenoma is exceptional. [2] We report a case of fibroadenoma with coexisting IDC and extensive duct carcinoma in situ (DCIS) in a woman with surgical menopause.A 43-year-old woman underwent hysterectomy and bilateral salpingo-oophorectomy in March 2005, for multiple leiomyomata and ovarian follicular cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Therefore, histological diagnosis is typically unexpected (1,8,9,13,14). The mean age of patients with carcinoma in FA has been reported as 42-44 years, ~20 years subsequent to the peak age of occurrence of FA (15,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, histological diagnosis is typically unexpected (1,8,9,13,14). The mean age of patients with carcinoma in FA has been reported as 42-44 years, ~20 years subsequent to the peak age of occurrence of FA (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Malignant transformation within FA is unusual, reported to be 0.1-0.3% in a screened population. However, the number of real cases appears to be even rarer; histological diagnosis is typically unexpected following excision of a breast lesion, with only >100 cases reported in the literature thus far (8,9). Classic lobular carcinoma in situ (LCIS) is a type of lobular neoplasia and is diagnosed when >50% of the acini of a lobular unit are distended and distorted by a dyshesive proliferation of cells with small, and uniform nuclei (10).…”
Section: Introductionmentioning
confidence: 99%
“…Lobular or ductal invasive or noninvasive cancer can be observed together with fibroadenoma. Although around two-third of these cancers are lobular and one-third is ductal or mixed, the rates of lobular and ductal carcinoma in situ are equal (2,6). In this study, it was identified that invasive ductal carcinoma developed from fibroadenoma epithelial components.…”
Section: Discussionmentioning
confidence: 84%
“…In addition to developing within the fibroadenomas, invasive carcinoma can hold onto the fibroadenomas itself by originating from the neighboring breast tissue. The literature reports that the epithelial component can develop into a carcinoma in situ and invasive cancer (3)(4)(5)(6). Manukyan et al (7) have reported a case of ductal carcinoma in situ that has developed within fibroadenomas itself.…”
Section: Introductionmentioning
confidence: 99%
“…Although, fibroadenoma is generally considered benign, there is evidence for an association with an increased risk of invasive breast cancer 4. Furthermore, progression of the epithelial component to carcinoma in situ and invasive carcinoma has been documented in the literature 58. Malignant transformation from fibroadenoma to cancer is rare.…”
Section: Introductionmentioning
confidence: 99%